Microstructure and Properties of a 2.25Cr1Mo0.25V Heat-Resistant Steel Produced by Wire Arc Additive Manufacturing. (7th April 2020) - Guo, Chun; Liu, Suhang; Hu, Ruizhang; Liu, Chunhui; Chen, Feng
Abstract : Wire arc additive manufacturing (WAAM) technology was used to produce samples of a 2.25Cr1Mo0.25V heat-resistant steel. The phase composition, microstructure, and crystal structure of the investigated material in the as-cladded state and postcladding heat-treated (705°C × 1 h) state were analysed by optical emission spectrometry (OES), optical microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The properties of the investigated material in the as-cladded state and postcladding heat-treated (705°C × 1 h) state were determined by a microhardness tester, mechanical properties tester, and Charpy impact tester. Through a study of the microstructure and properties, it is found that the investigated material produced by WAAM exhibits good forming quality and excellent metallurgical bonding properties, and no obvious defects are found. The microstructure consists mainly of Bg (granular bainite) and troostite precipitated at the grain boundaries. The results from high-resolution transmission electron microscopy observations show that the crystal structures of the 2.25Cr1Mo0.25V heat-resistant steel samples produced by WAAM in the as-cladded condition have many defects, such as dislocations and martensite-austenite (M-A) constituents, and their grain edges are sharp. There is a dramatic decrease in the dislocations in the 2.25Cr1Mo0.25V heat-resistant steel samples produced by the WAAM condition after the postcladding heat treatment (705°C × 1 h), and the grains become smooth. The distribution of the microhardness in the longitudinal and transverse cross sections of the samples is very uniform. The average longitudinal and transverse microhardness of the samples in the as-cladded state is 310 HV0.5 and 324 HV0.5, respectively. The average longitudinal and transverse microhardness of the samples after post-cladding heat treatment is 227 HV0.5 and 229 HV0.5, respectively. The yield strength of the samples without a postcladding heat treatment is 743 MPa, the tensile strength is 951 MPa, the elongation is 10%, and the Charpy impact value at -20°C is 15 J. After the postcladding heat treatment, the yield strength, tensile strength, elongation, and Charpy impact value of the samples are 611 MPa, 704 MPa, 14.5%, and 70 J, respectively.